Marketing Strategy of the Residential Real Estate Construction Entities in the Consumer Market - Biletskyi Ihor V. (Problemi Ekonomiki, 2022)
The purpose of the study is to determine the marketing characteristics of the activities of entities in the field of residential real estate construction and to formulate proposals for the development of an adequate instrumentarium for the implementation of the marketing complex within the terms of the current challenges of the external environment. The analysis of the available scientific literature made it possible to obtain a conclusion about the fragmentary nature of research in the specified sector of economic relations and to attribute the aspects of the systemic implementation of the marketing complex in the activities of construction companies to the current issues. The fundamental differences of construction products from mass or series production of goods are revealed as a starting point of the research. The search for modification options for the use of classic marketing tools to influence the behavioral patterns of potential consumers in the residential real estate market in the B2C segment was carried out using the methodology of the 4P conception or marketing-mix. Decomposing spheres of influence into such elements as Product, Price, Place, Promotion made it possible to obtain applied results. The identification of the product niche of the construction company is recognized as a system-forming aspect in building a marketing strategy and the corresponding tactics. Attention is focused on the need for deep differentiation of the offer according to the criterion of the sales region, using the instruments of persuasion regarding the current and future potential of the successful functioning of the object according to its intended purpose, strengthening the emotional content of the offer, shifting the vector regarding the construction of communication channels into the digital environment. Variants of effective strategies for responding to challenges from the transformed external environment in the coordinates of Marketing 3.0, 4.0, 5.0 concepts are revealed, such as: implementation of the green construction system as one of the ways to maintain the balance between human needs, financial indicators and the environment; creation of a favorable reputation for the company, a positive corporate image by initiating and participating in social or charitable events.